Light scattering study of irregular particles with arbitrary size, shape, and complex refractive index - Gautam, Prakash (Kansas State University, 2022)
We investigated light scattering due to irregularly shaped aerosol particles with diverse shapes, sizes, and complex refractive indices. We have designed and developed a light scattering setup based on a novel optical scheme that can detect light from 0.32° and 177.6°, from an extreme forward to the backscattering regime, involving 46 angles. Our setup was able to measure all six independent scattering matrix elements; however, we focused on measuring the scattering intensity and the linear depolarization ratio for different dust particles. Given the extremely small and large angles, the data obtained for our setup are plotted on both: versus scattering angle, θ linearly, and scattering wave vector, q or qR with R the radius of a particle, on a log-log scale, called θ and Q-space respectively. The Q- space analysis best represents the data at the extreme forward scattering regime; however, it compresses the data at the large scattering angles, θ , where useful data also reside. At large scattering angles, the scattered intensity is best viewed by θ-space analysis. We scattered the light from different aerosol particles viz; silicon dioxide (SiO₂), aluminum abrasive (Al₂O₃), a highly refractive molybdenum disulfide (MoS₂), a highly absorptive hematite particle (α−Fe₂O₃), arizona road dust and Soot particles. The measured scattered intensity was interpreted by applying both analysis methods. Light scattering for all particle types was compared to theoretical Mie scattering calculations using size distributions determined by an Aerodynamic Particle Sizer (APS 3321), an aerosol measuring instrument. The compared results between the experimentally measured data and Mie calculations showed a close agreement at the forward scattering regime and poorly at the side and backscattering regimes. Effects of the intensity-weighted size distribution were discussed. We applied Guinier analysis on light scattering measured data to compare light scattering inferred size to the intensity-weighted mean sizes for all shape particles. The light scattering sizes were consistent with the intensity-weighted mean sizes of reasonable accuracy for any shape and refractive index. This result has demonstrated the importance of intensity weighting of the size distribution in light scattering. We measured and studied the linear depolarization ratio for different dust particles. They all displayed a common pattern. The measured values were negligibly small at the forward scattering regime. They increased with increasing the scattering angle and reached a maximum at the side scattering regime that generally droped off at the backscattering regime. The effects of particle asphericity, size, and refractive index on the linear depolarization ratio were investigated. We further investigate the light scattering from fractal soot and non-fractal hematite aggregates. The results showed an enhancement in the backscattering despite a large imaginary refractive index. We found that enhancement backscattering for the non-fractal aggregate is due to internal multiple scattering between the grains within the aggregate. In contrast, enhancement backscattering is yet to be understood for fractal soot aggregates. Furthermore, the results presented in this work showed the sensitive of light backscattering with the change in particles’ shapes, sizes, and refractive indices and warn the experimentalist to use the backscattering measured data with great caution.
Keywords: Aerosol particles; Optical setup; Light scattering; Q-space analysis; Aggregates; Soot particles